Vous êtes sur la page 1sur 3

Fogler_AppA.3_Web.

fm Page 1 Thursday, December 17, 2015 6:03 PM

Web Appendix A.3

A.3 Solutions to Differential Equations

A.3.A First-order Ordinary Differential Equations

Also see http://www.ucl.ac.uk/Mathematics/geomath/level2/deqn/de8.html

dy
+ f (t ) y = g (t ) (WA.3.A.1)
dt

Integrating factor = exp ( ∫ fdt )


Multiply through the integrating

e∫ + e ∫ y = e ∫ g (t )
f ( y ) dt dy fdt fdt

dt
Collect term

⎛ ye ∫ fdt ⎞
⎟ = e ∫ g (t )
fdt
d⎜
⎜⎝ dt ⎟⎠

ye ∫ = ∫ g (t ) e ∫
fdt fdt
dt + K1

and divide by e ∫
fdt

y = e ∫ ∫ g ( t ) e ∫ dt + K1e ∫
− fdt fdt − fdt
(WA.3.A.2)

1
Fogler_AppA.3_Web.fm Page 2 Thursday, December 17, 2015 6:03 PM

2 Web Appendix A.3

Example A.3–1 Integrating Factor for Series Reactions

dy
+ k2 y = k1e− k1t
dt

Integration factor = exp ∫ k2 dt = e− k2 t

dyek2 t
= ek2 t k1e− k1t = k1e( k2 − k1 )t
dt

k1
ek2 t y = k1 ∫ e( k2 − k1 )t dt = e( k2 − k1 )t + K1
k2 − k1

k1
y= e− k1t + K1e− k2 t
k2 − k1

t=0 y=0

k1
y= ⎡ e− k1t − e− k2t ⎤⎦
k2 − k1 ⎣

A.3.B Coupled First-order Linear Ordinary Differential Equations


with Constant Coefficients

Also see http://www.mathsci.appstate.edu/~sjg/class/2240/finalss04/Alicia.html.


Consider the following coupled set of linear first order ODE with con-
stant coefficients.

dx Or in Matrix Notation
(1) = ax + by t=0 x = x0
dt
⎡ dx ⎤
⎢ dt ⎥ ⎡ a b ⎤ ⎡ x ⎤
dy ⎢ ⎥=⎢ ⎥⎢ ⎥
(2) = cx + dy t=0 y = y0 ⎢ dy ⎥ ⎣ c d ⎦ ⎣ y ⎦
dt ⎢⎣ dt ⎥⎦
The solution to these coupled equations is

x = Ae−αt + Be−βt (3)


and

y = K1e−αt + K 2 e−βt (4)

where

⎡ TrA ± TrA 2 − 4 DetA ⎤


α, β = − ⎢ ⎥ , TrA = a + d , DetA = ad − bc
⎢⎣ 2 ⎥⎦
Fogler_AppA.3_Web.fm Page 3 Thursday, December 17, 2015 6:03 PM

Web Appendix A.3 3

From the initial conditions

t=0 x = x0 and y = y0 we get

x0 = A + B
and

y0 = K1 + K 2

differentiating equations (3) and (4) and evaluating the derivative at t = 0

dx ⎞
⎟ = −αA − βB = ax0 + by0
dt ⎠ t = 0

dy ⎞
⎟ = −αK1 − βK 2 = cx0 + dy0
dt ⎠ t = 0
We have four equations and four unknowns (The arbitrary constants of inte-
gration A, B, K1 and K2) so we can eliminate these arbitrary constants of
integration.
If y0 = 0 then the solution takes the form

⎡ ( a + α ) e−βt − ( a + β ) e−αt ⎤
x = x0 ⎢ ⎥
⎣ α−β ⎦

cx0 −βt cx0 −αt


y= e − e
α+β α+β